Avian species of Sungai Sedim Forest Eco Park: Boost for ecotourism activities (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Sungai Sedim Forest Eco Park is a forest amenity situated within the Gunung Inas Forest Reserve in Peninsular Malaysia, known for its abundant biodiversity and ecotourism activities. The ongoing documentation of fauna richness in the amenity forest could be a crucial element for supporting conservation and promoting sustainable tourism development. Hence, this study aimed to document avian species richness and highlight its role in enhancing ecotourism activities at Sungai Sedim Forest Eco Park. Bird surveys were conducted over five sessions from July 2022 to October 2022, utilizing mist-netting, direct observation, and bird vocalizations. The surveys successfully identified a total of 61 species belonging to 30 families. The diversity indices consistently indicated high species diversity across sessions (Shannon index: 2.045 - 3.912), with peak richness occurring in the fourth session. These findings highlight that Sungai Sedim Forest Eco Park supports a rich and dynamic bird community, reinforcing its significance as a birdwatching destination. Continuous biodiversity monitoring is therefore essential, both to safeguard ecological integrity and to provide a scientific foundation for sustainable ecotourism planning in Malaysia.
Keywords: Avitourism; environmentally sensitive areas; species richness